Mechanisms underlying induction of allergic sensitization by Pru p 3. Issue 11 (14th July 2017) - Tordesillas, L.; Cubells‐Baeza, N.; Gómez‐Casado, C.; Berin, C.; Esteban, V.; Barcik, W.; O'Mahony, L.; Ramirez, C.; Pacios, L. F.; Garrido‐Arandia, M.; Díaz‐Perales, A.
Summary: Background: Recently, the nature of the lipid‐ligand of Pru p 3, one of the most common plant food allergens in southern Europe, has been identified as a derivative of the alkaloid camptothecin bound to phytosphingosine. However, the origin of its immunological activity is still unknown. Objective: We sought to evaluate the role of the Pru p 3 lipid‐ligand in the immunogenic activity of Pru p 3. Methods: In vitro cultures of different cell types (monocyte‐derived dendritic cells [moDCs], PBMCs [peripheral blood mononuclear cells] and epithelial and iNKT‐hybridoma cell lines) have been used to determine the immunological capacity of the ligand, by measuring cell proliferation, maturation markers and cytokine production. To study the capacity of the lipid‐ligand to promote sensitization to Pru p 3 in vivo, a mouse model of anaphylaxis to peach has been produced and changes in the humoral and basophil responses have been analysed. Results: The lipid‐ligand of Pru p 3 induced maturation of moDCsc and proliferation of PBMCs. Its immunological activity resided in the phytosphingosine tail of the ligand. The adjuvant activity of the ligand was also confirmed in vivo, where the complex of Pru p 3‐ligand induced higher levels of IgE than Pru p 3 alone. The immunological capacity of the Pru p 3 ligand was mediated by CD1d, as maturation of moDCs was inhibited by anti‐CD1d antibodies and Pru p 3‐ligand co‐localized with CD1d on epithelial cells. Finally, Pru p 3‐ligand presented by CD1d was able to interact with iNKTs. Conclusions and Clinical Relevance: The Pru p 3 lipid‐ligand could act as an adjuvant to promote sensitization to Pru p 3, through its recognition by CD1d receptors. This intrinsic adjuvant activity of the accompanying lipid cargo could be a general essential feature of the mechanism underlying the phenomenon of allergenicity.